Strategi Guru Dalam Mengembangkan Soft Skill Siswa Pada Mata Pelajaran Aqidah Akhlak Di Kelas X MA Darussalam Kota Bengkulu - M. Herlambang M. Herlambang; Edi Ansyah; Masrifa Hidayani (GHAITSA : Islamic Education Journal, 2021)
The problem that exists in this study is how the teacher's strategy in developing students' soft skills in the Aqidah Morals subject in class X MA Darussalam Bengkulu City, the factors that influence the teacher's strategy in developing students' soft skills in the Aqidah Morals subject in class X MA Darussalam Bengkulu City. The method used in this research is a case study where the researcher tries to find out the Soft Skill Development Strategy of Students in Islamic Religious Education Learning at MA Darussalam Bengkulu City. Based on the results of the study, it can be concluded that the development of students' soft skills by creating a character model to be developed, teachers must help children in adopting the ability to understand and master soft skills, teachers must be able to create an atmosphere that can develop soft skills, and provide various kinds of activities that are based on values. life and the rules to be learned. Factors supporting the development of soft skills in terms of student motivation and intelligence. In terms of social factors Supporters of soft skill development are seen from the involvement of parents and the surrounding environment, the inhibiting factor for soft skill development in terms of individual factors is the inhibiting factor seen from maturity or growth and from a social point of view, it is seen from the association with peers and its relationship with social media